KEANEKARAGAMAN JENIS SERANGGA PADA KOMUNITAS MANGROVE DI PULAU HOGA KABUPATEN WAKATOBI PROVINSI SULAWESI TENGGARA - Suriana, Suriana; Jamili, Jamili; Rahman, Rahman (Jurnal BioWallacea, 2015)
The aims of this research were determine diversity and evenness index of insect atHoga Island Wakatoby Regency. This research used the mehtod of squared plot. It is wasmade 3 pieces purporsively line transect direct shoroline cut mangrove communities startfrom the most advanced (seaward) direction behind. Each transect plots observations weremade on the left and the right along the transects line. The diversity index and evennessindex was determined using Shanon-Wiener. The result showed that, there were 4 orders ofinsects which consist of 7 families and 13 genera. The highest diversity index (Hâ) of inscetswas found at Osbornia clodonata stand (0.25), while it was the lowest at Xilocarpusgranatums stand (0.14). Evenness index (E) of insect among has significance different all ofmangrove stands, namely a stand Bruguiera gymnorrizha (0.09), Pemphis accidula (0.07),Osbornia clodonata (0.12) and Xilocarpus granatum (0.07).Keywords : Diversity, Insects, Mangrove Community, Hoga Island